Antinociceptive and Behavioral Effects of Methadone Alone or in Combination with Detomidine in Conscious Horses - Oliveira, Flávia A. de; Pignaton, Wangles; Teixeira-Neto, Francisco J.; Queiroz-Neto, Antônio de; Puoli-Filho, José N. P.; Scognamillo, Márcia V. R.; Viveiros, Bruno M.; Luna, Stélio Pacca Loureiro [UNESP] (Elsevier, 2013)
The antinociceptive and behavioral effects of methadone (MET) alone or combined with detomidine (DET) were studied in horses. Intravenous treatments were randomly administered in a two-phase crossover study. In phase 1, six horses were treated with saline (control) or 0.2 or 0.5 mg/kg methadone (MET0.2; MET0.5, respectively). In phase 2, six horses were treated with 0.01 mg/kg DET alone or with DET combined with 0.2 mg/kg MET (DET/MET0.2). Thermal nociceptive threshold (TNT) and electrical nociceptive thresholds (ENT) were recorded by using a heat projection lamp and electrodes placed in the coronary band of the thoracic limbs, respectively. Spontaneous locomotor activity (SLA) was studied by movement sensors in the stall (phase 1). Chin-to-floor distance was assessed in phase 2. In phase 1, the TNT increased significantly for 30 minute after MET0.5 but not after saline or MET0.2. Hyperesthesia and ataxia were observed in 2 of 6 and 6 of 6 horses after MET0.2 and MET0.5, respectively. SLA increased significantly for 120 minutes after MET in a dose-dependent way, but not after placebo. In phase 2, DET and DET/MET0.2 significantly increased the TNT and ENT above baseline for 15 and 30 minutes, respectively; thresholds were significantly higher with DET/MET0.2 than with DET at the same times. Chin-to-floor distance decreased significantly from baseline for 30 minutes, and no excitatory behavior was observed in both treatments. Although the higher dose of MET induced short-acting antinociception, the associated adverse effects may contraindicate its clinical use. The lower dose of MET potentiated DET-induced antinociception without adverse effects, which might be useful under clinical circumstances. © 2013 Elsevier Inc. All rights reserved.
Keywords: Alpha-2 agonist; Analgesia; Horse; Opioid